Experiences of discrimination and its impacts on well‐being among racialised LGBTQ+ newcomers living in Waterloo region, Ontario, Canada. (10th February 2022) - Cox, Emily; Warren, Teneile; Khan, Maryam; Wilson, Ciann; Cameron, Ruth; Davis, Charlie; Coleman, Todd; Steffler, Jeremy; Coulombe, Simon; Woodford, Michael
Abstract: Discrimination (i.e. racism, homo/bi/transphobia) at both the individual and systemic levels may negatively impact the well‐being of racialised LGBTQ+ newcomers living in Waterloo Region, Ontario, Canada. Current research about the experiences of LGBTQ+ newcomers focuses predominantly on homogeneous samples of gay men living in large metropolitan city centres. The present study aims to extend the current literature by exploring the experiences of discrimination and its impacts on well‐being among racialised LGBTQ+ newcomers living in a small urban area and representing a variety of intersecting identities (i.e. ethno‐racial background, LGBTQ+ identity, newcomer status). Using a qualitative method, 10 individuals were invited to complete a semistructured interview between fall 2019 and summer 2020 about their experiences of discrimination in Waterloo Region, and how such experiences impact their well‐being. Using an intersectional lens, a thematic analysis revealed that racialised LGBTQ+ newcomers experienced discrimination before and after settlement in Waterloo Region. Prior to settlement, participants spoke predominantly about experiences of homo/biphobia and the associated feelings of internalised oppression. Alternatively, upon settling in Waterloo Region, experiences of discrimination were predominantly racism, and, in particular, systemic racism, which manifested as an inability to access adequate services and a lack of representation in various spaces throughout Waterloo Region. These results extend previous research by identifying the service barriers experienced by racialised LGBTQ+ newcomers living in a small urban area and can be used to inform best practices for addressing these barriers in Waterloo Region and other small urban areas with similar demographics. Implications and limitations are discussed.